(untitled) (Fiep Bulletin - online, 2016)
This article will discuss the five components of physical fitness related to health, which are: muscular strength, muscular endurance, cardio-respiratory endurance, flexibility and body composition; showing his concepts, classifications, influencing factors and its importance for health. Weineck (1991) describe the overall strength and local strength, says about the first: "force level developed of the major muscle groups (muscles of the trunk and extremities)"; and on the second, "use of isolated muscles or muscle groups." Flexibility is the "physical quality responsible for voluntary execution of a maximum angular range of motion of a joint or group of joints, within the morphological boundaries without the risk of causing injury." (Dantas, 1999: 57). Muscular endurance is the "ability of the muscles to supply a submaximal force repeatedly." (NIEMAN, 1999). Cardiorespiratory endurance is "When large muscle masses of the body are involved in a continuous, rhythmic activity, circulatory and respiratory systems increase its activities to provide enough oxygen to burn fuel and provide energy to the muscles that are working." (NIEMAN, 1999). According to Nieman (1999) body composition is the proportion of fat in relation to lean body weight, often expressed in percentage of body fat, or even relative amounts of body fat and lean body tissue or lean body mass (muscle, bone, water, skin, blood and other non-adipose tissues).